Visual Loss Due to Optic Nerve Injury with Blunt Trauma: A Case Series: Doi: 10.36351/pjo.v40i2.1748 - Bodla, Afzal; Maria Afzal Bodla; Nalain syedah (Pakistan Journal of Ophthalmology, 2024)
Vision impairment resulting from optic nerve damage poses a significant clinical challenge, often stemming from both direct and indirect traumatic injuries. In this article, we address the complexities involved in diagnosing and managing optic nerve damage, particularly in cases of blunt trauma-induced compression. We highlight the potential delay in diagnosis due to concurrent life-threatening conditions and the difficulties in assessing severely affected patients. Additionally, we present a case series involving three individuals who experienced vision loss secondary to optic nerve compression following blunt trauma. Through this analysis, we underscore the importance of timely recognition and appropriate management strategies in optimizing outcomes for patients with optic nerve injuries.